Outlines of English history from B.C. tot A.D. 1926 with genealogical tables and short biographical sketches - Carter, George (London : Relfe Brothers, 1926)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: politieke geschiedenis; politieke figuren; Groot-Brittannië.